The cognitive test anxiety level among undergraduates with musical instrument background - Hue, Chi Yin; Ahmad, Nor Aniza (Faculty of Educational Studies, Universiti Putra Malaysia, 2016)
Cognitive test anxiety was a raising issue in education field and also one of the factors that associated with university students’ academic result. This research focused on the level of cognitive test anxiety between undergraduates with Western and Chinese musical instrument background. Besides, it also studied the differences between the groups of musical instrument background on cognitive test anxiety. In this research, total 109 respondents were randomly selected from the music society of public university UPM, UKM and UM. There were 54 undergraduates with Western musical instrument background and the rest with Chinese musical instrument background. In this quantitative research, respondents were required to answer a short demographic questionnaire and Cognitive Test Anxiety Scale Revised (CTAR-25) questionnaire which measured cognitive test anxiety. The descriptive statistic has showed that undergraduates with musical instrument background have moderate level of cognitive test anxiety M = 52.39, SD = 12.06. High level of cognitive test anxiety indicated negative thoughts such as comparing self-performance to peers, considering the consequences of failure and low level of confidence in performance (Cassady & Johnson, 2002). Besides, the independent t test result has showed that there was no significant difference between the undergraduates with Western (M = 52.91, SD = 12.17) and Chinese (M = 51.89, SD = 12.05; t (107) = .438, p = .662, two tailed) musical instrument background on cognitive test anxiety. There was a weak and negative correlation between the years of experience in musical instrument background and cognitive test anxiety, in other words, the more experience in playing musical instrument, the less cognitive test anxiety that undergraduates exhibits. However, the result was not statistically significant, r = -.108, n = 109, p = .265.